Characterization of Lithium Tantalate (LiTaO3) Film on the Concentration Variations of Ruthenium Oxide (RuO2) Dope. Issue 201 (2nd September 2019) - , Irzaman; Prawira, Dezya Salsabila, Irmansyah; Yuliarto, Brian; Siregar, Ulfah Juniarti
Abstract: One of the ferroelectric materials that has a large potential to be developed is LiTaO3 film. LiTaO3 film has been successfully produced by doping with RuO2 concentrations of 0%, 2%, 4%, and 6% using the CSD (Chemical Solution Deposition) method with a spin coating technique at 8000 rpm and an annealing temperature of 850° C. Samples were characterized using UV-Vis Spectrophotometry, SEM, XRD, and EDX. The film thicknesses at dope concentrations of 0%, 2%, 4%, and 6% 0.2681 µm, were 0.2234 µm, 0.2234 µm, and 0.5078 µm, respectively, with bandgap energy levels of 2.38 eV, 2.29 eV, 2.04 eV, and 2.47 eV. The lattice parameters obtained were a = 5.098961 Å and c = 14.316897 Å (0% RuO2 ), a = 5.065135 Å and c = 14.058488 Å (2% RuO2 ), a = 5.069937 Å and c = 114.275256 Å (4% RuO2 ), and a = 5.058727 Å and c = 14.253829 Å (6% RuO2 ) causing the crystal structure to be hexagonal (α = β = 90° and γ = 120°) with crystal sizes for each film 0.258 µm, 0.285 µm, 0.295 µm, and 0.36 µm.